Meiotic behavior and pollen fertility in triploid and tetraploid natural populations of Campuloclinium macrocephalum (Eupatorieae, Asteraceae) - Farco, Gabriela Elizabeth (2014)
Campuloclinium macrocephalum DC. is a perennial herb widely distributed in the New World and introduced in South Africa, where it is commonly called ‘‘pompom weed’’. This species is considered one of the most important weeds of Brazil and one of the problematic invasive plants of South Africa. The meiotic system can be studied to assess the ability of a weed to spread, but only few studies on C. macrocephalum have been realized. In this study, we examined the meiotic behavior and pollen fertility of 14 natural populations of C. macrocephalum from Argentina and Uruguay. Meiotic analysis revealed 2 triploid (2n = 3x = 30), 11 tetraploid (2n = 4x = 40) and 1 mixed population (2n = 2x = 20, 2n = 4x = 40). Both, triploid and tetraploid specimens showed a widely variable meiotic behavior with irregular chromosome pairing showing univalents, bivalents, trivalents (in triploids) and tetravalents (in tetraploids) at diacinesis of first meiotic division. Different abnormalities were observed, such as: laggard chromosomes, chromatin bridges, and out of plate chromosomes at metaphase I. During meiosis I (prophase), some cells showed the phenomenon of cytomixis or chromatin transfer between pollen mother cells. The meiotic indexes suggest that only four populations were normally fertile (over 90 % of fertile pollen), indicating meiotically stable plants. The remaining populations share variable pollen fertility, with triploids ranging from 46.64 to 54.83 % and tetraploids varying from 3.54 to 45.30 %. We suggest that polyploidy seems to be recurrent in C. macrocephalum, promoting partial sterility of pollen grains, generating large numbers of individuals by apomixis promoting invasion of crop fields. This study presents the meiotic behavior of this weed, these could be useful for future studies of biological control in areas with no natural enemies.